Determination of host status of citrus fruits against the Mediterranean fruit fly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) - Staub, G; De Lima, F.; Majer, Jonathan (Blackwell Publishing Asia, 2008)
The Mediterranean fruit fly (Medfly), Ceratitis capitata (Wiedemann) is a pest of citrus in parts of Western Australia. Three citrus cultivars: Valencia oranges, Eureka lemons and Imperial mandarins, as well as non-citrus control fruits, were examined for attractiveness and suitability to Medfly in the field and in the laboratory using choice and no-choice experiments. Oranges were more susceptible to Medfly than mandarins and lemons. Punctures in the skin had a significant impact on the degree of infestation in both citrus and non-citrus control fruit. Artificial infestation and larval survivorship were used to investigate the suitability of each cultivar to Medfly under laboratory conditions. Oranges and mandarins were suitable for the development of Medfly, but lemons were a poor host. When each cultivar was in season, field cage trials demonstrated that infestation occurred in oranges and mandarins but not in lemons.